2020
DOI: 10.12669/pjms.36.6.2945
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of different doses of atorvastatin combined with febuxostat in patients with gout and carotid atherosclerosis

Abstract: Objective: To evaluate the efficacy of atorvastatin combined with febuxostat in the treatment of gout patients with carotid atherosclerosis and to observe the effects on serum tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and C-reactive protein (CRP) levels, carotid plaques, and the adverse reactions. Methods: Seventy patients with gout and carotid atherosclerosis admitted to Affiliated Hospital of Hebei University from January 2014 to June 2017 were randomly divided into a treatment group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This, in turn, forms a vicious cycle of hyperuricemia and subsequently triggers or aggravates cardiovascular disease ( 59 ). Moreover, several studies have confirmed that SUA-lowering therapy can improve outcomes of patients with a cardiovascular or cerebrovascular disease to a certain extent ( 60 ).…”
Section: Discussionmentioning
confidence: 98%
“…This, in turn, forms a vicious cycle of hyperuricemia and subsequently triggers or aggravates cardiovascular disease ( 59 ). Moreover, several studies have confirmed that SUA-lowering therapy can improve outcomes of patients with a cardiovascular or cerebrovascular disease to a certain extent ( 60 ).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, when comparing the changes of BP and blood lipids, we found that the BP improvement of patients in the study group was more significant, which also shows that AP + ATO is more suitable for EH patients with CA. ATO, one of the most commonly used drugs for regulating blood glucose and blood lipids in clinical practice, can reduce cholesterol synthesis, increase LDL receptor synthesis, and reduce blood cholesterol and LDL-C levels [ 16 ]. The protein binding rate of ATO is about 98%, most of which are excreted in the bile in the form of metabolites, with relatively stable drug safety.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, during the treatment was reduced a level of total cholesterol, although not statistically signifi cant. There is evidence in the current literature of the eff ects of urate-lowering therapy on atherosclerosis, for instance, a study work of 2020 showed that a double dose of atorvastatin in combination with febuxostat can eff ectively reduce uric acid level, improve the "infl ammatory profi le" of patients and infl uence carotid plaques without increasing side eff ects [10]. It is known that uric acid crystals activate NLRP3 infl ammasomes, leading to the formation of high levels of IL-1β and IL-18, which is characteristically to acute attacks of gout, and cholesterol activates the same infl ammasome before occurrence of atherosclerotic lesions [5][6][7].…”
Section:  Discussionmentioning
confidence: 99%
“…In addition, hyperuricemia correlates with number of infl ammatory parameters levels, such as white blood cell quantity, CRP, ESR, IL-6, IL-1, IL-18 and TNF [7,10,21], which are involved in the development of acute gout arthritis. In the current study, it was found a statistically signifi cant reduction of levels of infl ammatory parameters such as CRP and ESR.…”
Section:  Discussionmentioning
confidence: 99%
See 1 more Smart Citation